Sustainability Education as a Pathway to Minority Participation in STEM. (27th March 2020) - Xu, Cassie; Smerdon, Jason E.; DeFries, Ruth; Unwin‐Kuruneri, Natalie
Abstract: Sustainability education offers higher education institutions opportunities to broaden the participation of groups traditionally underrepresented in the Science, Technology, Engineering, and Mathematics (STEM) fields. This chapter focuses on an exploratory case study that looks at how sustainability education can be used as a tool to increase student engagement and participation in STEM at the undergraduate level and why it should be considered as an important tool for addressing diversity challenges.